Jenkins Essentials - Soni, Mitesh; Soni, Mitesh (Packt Publishing, 2017)
Develop a base for DevOps culture by implementing Continuous Integration and Continuous Delivery including automated builds, unit test execution, packaging, and static code analysis with Jenkins 2About This BookExplore Continuous Integration and automation, along with how to manage and configure JenkinsMaster using Jenkins to build, test, and package Java applicationsLearn about Jenkins' extensible features with automated deployment on cloud platforms such as AWS Elastic Beanstalk and Microsoft Azure App ServicesLearn about creating a pipeline using Build Pipeline plugin and the Pipeline as Code feature available after the release of Jenkins 2.0Who This Book Is ForIf you are a Jenkins novice or beginner with a basic or no understanding of Continuous Integration, then this is the book for you. Beginners in Jenkins will get quick hands-on experience and gain the confidence to explore the use of Jenkins further.What You Will LearnGet to grips with the challenges faced by developer communitiesLearn about Continuous Integration and how it helps build various Java applicationsFacilitate the installation and configuration of JenkinsInstall and configure code repositories and build toolsLearn about the integration of Eclipse with JenkinsManage the integration of Jenkins, code repositories, and build toolsFamiliarize yourself with Continuous Integration for Java applications with unit test execution and static code analysisLearn about Continuous Delivery and how to deploy applications in AWS and Microsoft AzureIn DetailIn agile development practices, developers need to integrate their work frequently to fix bugs or to create a new feature or functionality. Jenkins is used specifically for Continuous Integration, helping to enforce the principles of agile development. This book focuses on the latest and stable release of Jenkins (2.5 and later), featuring the latest features, such as Pipeline as Code, the new setup experience, and the improved UI. With the all-new Pipeline as Code feature, you will be able to build simple or advanced pipelines easily and rapidly, hence improving your teams' productivity.This book begins by tackling the installation of the necessary software dependencies and libraries you'll need to perform Continuous Integration for a Java application. From there, you'll integrate code repositories, applications, and build tools for the implementation of Continuous Integration.Finally, you will also learn how to automate your deployment on cloud platforms such as AWS and Microsoft Azure, along with a few advanced testing techniques.Style and approachThis book provides simple, step-by-step instructions, taking you from start to finish in accomplishing real-world Continuous Integration and Continuous Delivery tasks.